Szkieletowe groby późnej fazy kultury przeworskiej z Czeladzi, pow. górowski. Uwagi o obrządku pogrzebowym kultury przeworskiej na Dolnym Śląsku - Bohr, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
The skeletal graves from Czeladź in Górowo county represent an interesting element of the burial rites in the late stage of the Przeworsk culture. One of the graves was equipped with ceramic utensils (both hand-formed and thrown on a potter’s wheel) as well as clips with bevelled hoops, which were probably analogous to artefacts discovered in other archaeological sites in Lower Silesia. Two of the graves contained no equipment typical of other Lower Silesian burials in the late Przeworsk culture. Perhaps the habit of not equipping the dead with any items should be attributed to the specific posthumous garment or shroud worn. The stones found in the graves were probably inspired by the Wielbark culture or the Scandinavians.